STRATEGI PENGEMBANGAN DAN ANALISIS SWOT PADA PT. GARUDA INDONESIA TBK - Supeni, Nely; Ningsih, Wiwik Fitria (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
The purpose of this research is to plan a creative and workable strategy for PT. Garuda Indonesia Tbk in an effort to respond to competition in the aviation market. This type of research is descriptive qualitative. Methods of data collection using literature study and data analysis used is a SWOT analysis. Based on the analysis of the Cartesian diagram shows that PT. Garuda Indonesia Tbk is included in quadrant II, which is supporting the Diversification strategy. The result of SO strategy analysis is that PT. Garuda Tbk must maximize the government's financial assistance program to restore the company's financial condition as well as to maintain the company's big name. The results of the ST strategy analysis are PT. Garuda Indonesia Tbk must maintain excellent facilities and services in order to face other aviation competitors. The results of the WO strategy analysis, namely the existence of a financial assistance program from the government, can also be used to improve the competence of company human resources. The results of the WT strategy analysis, namely PT. Garuda Indonesia Tbk must reduce operational costs while maintaining quality in order to be able to compete in the world of aviation.